Anatomy of the Superman: Gabriele D’Annunzio’s Response to Nietzsche - Härmänmaa Marja (MIT Press, 2022)
This essay explores D’Annunzio’s reception of Nietzsche—particularly his sociopolitical theory and idea of the Übermensch—as dramatized in his novel Le Vergini delle rocce (The Maidens of the Rocks). D’Annunzio’s attitude towards Nietzsche was complicated and contradictory, varying from fascination and rivalry to rejection 10 and negation: rather than a philosopher or master, he saw Nietzsche as a poet and soulmate. Like many writers and artists of fin-de-siècle Europe, D’Annunzio too was attracted by Nietzsche’s elitist social theory and Übermensch, of which he presents his own version especially in Maidens of the Rocks. In the 15 novel, the young aristocrat Claudio Cantelmo aspires to overcome himself. However, the fact that Cantelmo fails to achieve his dream of fathering a New King of Rome, reveals D’Annunzio’s deep skepticism about contemporary Italy as well as his own “decadent” soul.